The relationship between physical fitness parameters and technical execution in young rhythmic gymnasts - Kritikou, M.; Donti, O.; Bogdanis, G. C.; Theodorakou, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Faultless technical execution imposed on rhythmic gymnasts by the rules of the International Federation of Gymnastics (F.I.G) requires a high level of physical fitness parameters starting from a young age and continuing throughout a gymnast`s career. The age between 9-12 years is considered as a critical period for future rhythmic gymnasts` evolution as physical fitness considerations optimize long-term training adaptations (Faigenbaum et al., 2009). Therefore, the aim of this study was to examine the effect of physical parameters on technical execution score in rhythmic gymnasts aged 9-12 years. Methods: Nine rhythmic gymnasts (aged 9.0±1.4 years, training experience 5±1 years) all qualifiers of the all-around competition in the Greek national championship participated in this study. Technical execution was evaluated by two international judges according to the F.I.G Code of Points. The gymnasts underwent a series of physical fitness tests (body composition, active and passive flexibility, muscular power and endurance, agility and balance). Pearson`s correlation coefficient (r) was used to detect linear associations among technical execution and physical fitness parameters. Univariate analysis of variance (ANOVA) examined the prediction power of several interactions of covariates on technical execution final score. Results: There were significant correlations between the score of technical execution and balance, jump on the right leg and muscular endurance of the abdominals (0.737, 0.690 and 0.684 respectively, p<0.05). Balance on the ball of the foot, single leg jumping ability and muscle endurance of the abdominals best predicted the final score of technical execution (F=10.827, p=0.05). ICC of the total score for the two judges was r= 0.96, p.0.01. Discussion: It is concluded that balance on the ball of the foot, jump ability on one leg and muscle endurance of the abdominals best predict technical execution in young rhythmic gymnasts. Rhythmic gymnasts are required to execute many different techniques of turns, jumps, leaps and balances structuring their future technical development. The results of this study provide information to coaches and specialists to understand the physical parameters that are related more with gymnasts` technical skill acquisition.